Solution of an integral equation with a logarithmic kernel - C. Sampath; D. J. Jain (International Journal of Mathematics and Mathematical Sciences)
A simple independent integral equation technique is presented to solve an integral equation with a logarithmic kernel which governs solutions of many two-dimensional Dirichlet boundary value problems involving two coplanar and parallel infinite strips. The technique is further illustrated by an example.